ANALISIS YURIDIS TERHADAP PEMUNGUTAN RETRIBUSI PELAYANAN PEMAKAMAN DAN PENGABUAN MAYAT BERDASARKAN PERATURAN DAERAH KOTA MEDAN NOMOR 3 TAHUN 2013 - RORY EKA PUTRA SITEPU (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Bastari3. Utary Maharany Barus The results of the research show that the provisions in Article 14paragraph (1) and (2) in conjunction with Article 15 paragraph (1) of theRegulation of Medan Municipality No. 3/2013 concerning retribution on cemeteryand cremation service in Medan, the retribution collecting system on cemeteryand cremation service used is the official assessment system because it uses thestipulation letter of retribution on cemetery and cremation service. According toArticle 23 paragraph (1) and (2) in conjunction with Article 24 of the RegionalRegulation No. 3/2013, a stipulation letter of retribution on cemetery andcremation which is not paid 7 days after it is due will be given a warning letter bythe head of the agency and it has to be paid within the following 7 days.Keywords: Collecting, Retribution, Cemetery and Cremation.